Head and neck pain drawing area correlates with higher psychosocial burden but not with joint dysfunction in temporomandibular disorders: a cross-sectional study - Herpel, Christopher; Drusko, Armin; Schwindling, Franz Sebastian; Rammelsberg, Peter; Tesarz, Jonas (The journal of pain, 2023)
Head and neck pain drawings have been introduced as part of the diagnostic gold standard for temporomandibular disorders (TMD). We aimed to quantify the spatial extent of pain in TMD patients and to analyze its association with further clinical findings. In a cross-sectional study, 90 patients (median age = 38 years; n women = 68) were diagnosed according to the DC/TMD. Intra-articular disorders were either confirmed or rejected by magnetic resonance imaging. The patients shaded all painful areas in a sketch of the left and right side of a face. A grid template was placed over the drawings and each region that contained markings was scored as painful. The correlation between the calculated area and the psychosocial variables (DC/TMD axis II) as well as the influence of pain lateralization were investigated using Spearman correlation, Mann-Whitney-U and chi-square tests. Pain affected all facial areas but concentrated on the regions of the temporomandibular joint and masseter origin. Thirty-nine percent reported purely unilateral pain, which was associated with structural TMJ findings in 77% of cases. Individuals with bilateral pain and those with greater spatial spread of pain had significantly higher scores on all axis II variables, except for functional limitation of the jaw. - Perspective - Head and neck pain drawings can contribute to a stratification of TMD patients. A greater extent of pain as well as pain bilateralization is associated with higher levels of emotional distress, pain chronicity and somatization, but not with functional impairment. Unilateral reporting of pain is associated with more intra-articular disorders.
Online verfügbar: 20. Januar 2023, Artikelversion: 6. Juni 2023
Gesehen am 08.08.2023